Pretreatment lymphocyte-to-monocyte ratio as a prognostic factor and influence on dose-effect in fractionated stereotactic radiotherapy for oligometastatic brain metastases in non-small cell lung cancer patients - Chen, Tian; Tang, Mengqiu; Zhou, Yang; Wang, Zhepei; Li, Shiwei; Wang, Hongcai; Lu, Yangfang; Wang, Jinguo; Shen, Weiyu (Frontiers in Oncology, 2023)
Background Studies on the prognostic factors for patients with brain oligo-metastasis treated with fractionated stereotactic radiotherapy (FSRT) usually focus on the size of metastatic tumor and radiation dose. Some inflammatory indicators have predictive value in non-small cell lung cancer (NSCLC) with brain metastasis receiving stereotactic radiotherapy. However, the prognostic value of inflammatory indicators in NSCLC patients with brain oligo-metastasis treated with FSRT, and their effect on radiotherapy dose is unknown. Methods A total of 95 advanced NSCLC patients with brain oligo-metastasis who had undergone FSRT treatment at Ningbo Medical Center Lihuili Hospital between January 2015 and April 2022 were enrolled into the study. Neutrophil to lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR), lymphocyte to monocyte ratio (LMR), tumor diameter and biologically effective dose (BED10) were analyzed using Chi-square test. Univariate and multivariate Cox regressions were used to identify predictors of survival. Results Tumor diameter (< 2 cm), BED10 (≥ 48Gy) and LMR (≥ 4) were found to be independently associated with good intracranial local control survival (i-LCS) through multivariate analysis. The median i-LCS was longer in patients with 2 independent risk factors (tumor diameter ≥ 2 and LMR < 4) administered with BED10 > 53.6Gy compared with patients administered with BED10 ≤ 53.6Gy (20.7 months vs 12.0 months, P = 0.042). LMR ≥ 4 (P = 0.019) and positivity for driver gene mutations (P = 0.011) were independently associated with better overall survival (OS). Conclusions LMR is an independent prognostic factor of i-LCS and OS in NSCLC patients with brain oligo-metastasis treated with FSRT. Patients with tumor diameter ≥ 2 and LMR < 4 should be treated with BED10 greater than 53.6Gy.